Interactive iPhone/iPad App for Increased Tympanic Membrane Familiarity. (December 2016) - Samra, Sheena; Wu, Andrew; Redleaf, Miriam
Introduction: Otology relies on clinical examination to teach anatomy of the ear. The purpose of this report is to introduce the Buckingham Virtual Tympanum iPhone app as an adjuvant educational tool to teach the anatomical details of the tympanic membrane (TM). Materials and Methods: This app, available free at the Apple Store, was constructed using archival photographs of normal and abnormal TMs, stratified by difficulty. Each image has 4 labeled structures, linked to questions to encourage active learning. Third-year medical students then used the app to familiarize themselves with the TM. Results: The free app was readily accessible and functioned without technical issues. By being interactive, it forced the user into the role of active learner. This pilot study found that students who used the app understood images of the TM better than those who did not use it. Discussion: We introduce an interactive, iPhone-based smartphone application that we found to be a useful adjunct for teaching TM anatomy.